Biological and Physical Properties of a Modification Silicone Liner. Issue 1 (March 2020) - Gu, Huiru; Luan, Huiqin; Mo, Zhongjun; Song, iang; Fan, Yubo
Abstract: Silicone liners provide comfortability for amputees, meanwhile effectively protecting their skin surface and subcutaneous tissue. Silicone liners used in prosthetics are mainly used for filling, cushioning, and suspending a receiving cavity. At present, biological and mechanical properties of silicone liners in prosthetic cavity remain unclear, and the price is expensive for amputees. We improve the silicone material preparation process to reduce the price as well as to ensure the mechanics and biosafety of the material. Characterization of silicone liner surface, cellular toxicity of silicone liner, bacterial adhesion on the surface of silicone liner, and mechanical properties were evaluated and compared among commercial materials (sample A and B) and our improved silicone liner material (sample C). The water contact, the macroscopic surface and the calculated mechanical parameters have no significant differences among the three types samples. The extract of three types silicone liner have no cytotoxicity reactivity. Samples C markedly reduced the adhesion of E. coli compared with sample A. The improved silicone material preparation process ensured the biological and mechanical properties and reduced the price of these silicone liners, thereby increasing their potential as silicone liners of prosthetics cavity.